Wrasse fishery on the Swedish West Coast: towards ecosystem-based management. (10th March 2021) - Bourlat, Sarah J; Faust, Ellika; Wennhage, Håkan; Wikström, Andreas; Rigby, Kristie; Vigo, Maria; Kraly, Paul; Selander, Erik; André, Carl
Abstract: Fishing and translocation of marine species for use in aquaculture is widespread. Corkwing, goldsinny, and ballan wrasse ( Symphodus melops, Ctenolabrus rupestris, and Labrus bergylta ) are fished on the Swedish west coast for use as cleaner-fish in Norwegian salmon farms. Here, we aim to provide knowledge and recommendations to support ecosystem-based management for wrasse fisheries in Sweden. We compared fished and non-fished areas to test if current fishery levels have led to stock depletion. To gain insight on the role of wrasse in the algal belt trophic chain, we analysed the gut contents of goldsinny and corkwing using metabarcoding. Finally, we analysed the trophic interactions of wrasse and potential prey in a mesocosm study. We could not detect any signs of stock depletion or altered size structure in fished areas compared to the protected control area. Gut analyses confirmed both goldsinny and corkwing as non-specialized, omnivorous opportunists and revealed, with 189 prey taxa detected, a broader spectrum of prey than previously known. Common prey items included mesoherbivores such as small gastropods and crustaceans, but also insects and algae. We conclude that there are no visible signs of stock depletion at the current removal level of wrasses by the fishery. However, this emerging fishery should be closely monitored for potential cascading effects on the algal belt ecosystem, and our study could provide a baseline for future monitoring.